The Principal’s Effective Leadership - Sari, Supriatini Chandra (International Conference of Moslem Society, 2019)
The success or failure of an educational institution depends on the leader, the principal, because the principal is the spearhead of the continuity of an educational institution. Principal leadership is the ability that principals have to influence, mobilize, and inspire others by using strategies to voluntarily try to achieve goals. The principal who is effective in carrying out his duties is always committed to the school's vision as a guideline in managing and leading the school.